Impacto socioeconómico de las remesas en el cantón La Maná 2011- 2013 - Ganchozo Rivera, María Pamela (2016)
Migration, the cash flow arrived out to La Maná canton of Cotopaxi province of, are the most important aspects of this study, the analyzes clarify the socioeconomic characteristics, amounts, frequency and characteristics of migrants who send remittances, and their families who receive it. Also, it is important to know the evidence by appliying same surveys that feed the debate about the relationship between migration, cash flow and socioeconomic impact. The cash flows is basic household expenses, to a lesser extent it’s destined to productive investments and domestic savings marginally to precisely these flows would have little chance of being oriented to other activities that are not related to current spending family, because the head of household is abroad and the mother is caring for her children, who becomes the new head of household. The weak link of cash flow for development, are not the responsibility of the families of the migrants, but the security environment and economic and financial confidence in the country.....